2002
DOI: 10.1067/mtc.2002.120709
|View full text |Cite
|
Sign up to set email alerts
|

Normothermia does not improve postoperative hemostasis nor does it reduce inflammatory activation in patients undergoing primary isolated coronary artery bypass

Abstract: Normothermic systemic perfusion does not influence the clinical course or the extent of inflammatory and hemostatic activation in patients undergoing primary isolated coronary artery bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…The present analysis is a post-hoc comparison of data collected in a prospective randomized investigation 6 and the relatively small number of patients enrolled can limit the statistical power of the study. The failure to identify as predictors of postoperative AF some variables that have been linked with this arrhythmia in other series can in fact be the expression of the reduced statistical power of our series.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present analysis is a post-hoc comparison of data collected in a prospective randomized investigation 6 and the relatively small number of patients enrolled can limit the statistical power of the study. The failure to identify as predictors of postoperative AF some variables that have been linked with this arrhythmia in other series can in fact be the expression of the reduced statistical power of our series.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 During this period all patients scheduled to undergo isolated elective coronary artery bypass grafting (CABG) at our Institution were screened for inclusion. Exclusion criteria were: associated cardiac or noncardiac surgical procedures, age Ͼ80 years, single-vessel disease, emergent or urgent revascularization, left ventricular ejection fraction Ͻ0.30, carotid artery disease, previous cerebrovascular accident, chronic dialysis, hepatic failure, respiratory or renal insufficiency (defined respectively as a preoperative creatinine level Ն2.0 mg/dL and a preoperative pOՅ60 mm Hg or PCo 2 Ͼ50 mm Hg on room air and/or a preoperative FEV1Ͻ1.25 l or Ͻ75% of the normal value), hemorrhagic conditions, active infection and chronic anti-inflammatory and antifibrinolytic therapy.…”
Section: Patient Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is in accord with our findings in that reduced NO concentrations were found in HC patients until 24 h after the end of CPB. Treatment of patients with inhaled NO at low concentrations during and after bypass 17 , or with NO donor during reperfusion 13 , reduced myocardial injury 17 and the cardiac inflammatory reaction, as assessed by IL-6, IL-8 and TNF-a levels 13 . In line with this report, our study showed an association between systemically reduced NO production and increased duration of elevated cytokine levels in patients with hypothermia and crystalloid cardioplegia, although no significant differences were detected in clinical outcome between these patients and those with normothermia and blood cardioplegia.…”
Section: Discussionmentioning
confidence: 99%